Secrets of the chocolate house - Brackston, Paula (Brackston, Paula. Found things., 2019)
Brackston returns to the Found Things series with its sequel, Secrets of the Chocolate House. After her adventures in the seventeenth century, Xanthe does her best to settle back into the rhythm of life in Marlborough. She tells herself she must forget about Samuel and leave him in the past where he belongs. With the help of her new friends, she does her best to move on, focusing instead on the success of her and Flora's antique shop. But there are still things waiting to be found, still injustices needing to be put right, still voices whispering to Xanthe from long ago about secrets wanting to be shared. While looking for new stock for the shop, Xanthe hears the song of a copper chocolate pot. Soon after, she has an upsetting vision of Samuel in great danger, compelling her to make another journey to the past. This time she'll meet her most dangerous adversary. This time her ability to travel to the past will be tested. This time she will discover her true destiny. Will that destiny allow her to return home? And will she be able to save Samuel when his own fate seems to be sealed?